Предмет: Математика,
автор: shazikiss
6(x+1)+2(х-1)(х+х+1)-2(х+1)=26
Ответы
Автор ответа:
0
1) 6(x+1)+2(x-1)(x+x+1)-2(x+1)=26
6(x+1)+2(x+x+x-x-x -1)-2(x+1)=26
6x+6+2x+2x+2x-2x-2x-2-2x-2-26=0
6x-24=0
6x=24
x=4
x=2
6(x+1)+2(x+x+x-x-x -1)-2(x+1)=26
6x+6+2x+2x+2x-2x-2x-2-2x-2-26=0
6x-24=0
6x=24
x=4
x=2
Автор ответа:
0
(х+2)*-х(3х+1)*+(2х+1)(4х*-2х+1)=42
Похожие вопросы
Предмет: Математика,
автор: erlanaydariya
Предмет: Литература,
автор: momalas
Предмет: Українська література,
автор: istinnuuk
Предмет: Биология,
автор: Гена2003
Предмет: Обществознание,
автор: enofarovanatal